OneClick: A Framework for Measuring Network Quality of Experience - Chen, K.-T.; Tu, C.-C.; Xiao, W.-C. (IEEE INFOCOM 2009, 2009)
As the service requirements of network applications shift from high throughput to high media quality, interactivity, and responsiveness, the definition of QoE (Quality of Experience) has become multidimensional. Although it may not be difficult to measure individual dimensions of the QoE, how to capture users' overall perceptions when they are using network applications remains an open question. In this paper, we propose a framework called OneClick to capture users' perceptions when they are using network applications. The framework only requires a subject to click a dedicated key whenever he/she feels dissatisfied with the quality of the application in use. OneClick is particularly effective because it is intuitive, lightweight, efficient, time-aware, and application-independent. We use two objective quality assessment methods, PESQ and VQM, to validate OneClick's ability to evaluate the quality of audio and video clips. To demonstrate the proposed framework's efficiency and effectiveness in assessing user experiences, we implement it on two applications, one for instant messaging applications, and the other for first- person shooter games. A Flash implementation of the proposed framework is also presented.